Estimating average marginal effects in nonseparable structural systems - Susanne Schennach; Halbert White; Karim Chalak (Centre for Microdata Methods and Practice (cemmap), 2007)
We provide nonparametric estimators of derivative ratio-based average marginal effects of an endogenous cause, X, on a response of interest, Y , for a system of recursive structural equations. The system need not exhibit linearity, separability, or monotonicity. Our estimators are local indirect least squares estimators analogous to those of Heckman and Vytlacil (1999, 2001) who treat a latent index model involving a binary X. We treat the traditional case of an observed exogenous instrument (OXI)and the case where one observes error-laden proxies for an unobserved exogenous instrument (PXI). For PXI, we develop and apply new results for estimating densities and expectations conditional on mismeasured variables. For both OXI and PXI, we use infnite order flat-top kernels to obtain uniformly convergent and asymptotically normal nonparametric estimators of instrument-conditioned effects, as well as root-n consistent and asymptotically normal estimators of average effects.
Keywords: C13; C14; C31; 330; derivative ratio effect; endogeneity; indirect least squares; instrumental variables; measurement error; nonparametric estimator; nonseparable structural equation; Schätztheorie; Nichtparametrisches Verfahren; Methode der kleinsten Quadrate; Statistischer Fehler